Pendampingan Peningkatan Pengelolaan Ternak Jaya Menggunakan Sistem Informasi - I Made Pasek Pradnyana Wijaya; Luh Putu Safitri Pratiwi; M. Azman Maricar (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Ternak Jaya Farm is a small and medium enterprise (SME) engaged in the business of buying and selling pigs. The purpose of this community service activity is to improve the management of Ternak Jaya SME. Ternak Jaya Farm has not yet implemented a system for recording livestock development, health, or income and expenses from its business processes. To facilitate the management of the farm, a web-based information system was developed that aligns with Ternak Jaya’s business processes. The method used in this activity involved discussions and observations to understand the partner farm’s business processes in order to build the system. This community service activity resulted in an information system for recording pig farming activities, making it easier for the partner to document their farm operations. Training and direct assistance in using the system were provided to the partner to help them understand the system's features. The results of this community service show that the system developed has been successfully used by the partner to record livestock data and display the information they need. The initial objectives of the activity were achieved, and it is expected to assist the partner in managing their Ternak Jaya farm in the future.